LITOGEOQUÍMICA DAS ROCHAS GRANULÍTICAS DA REGIÃO DE IPIAÚ, SUL/SUDESTE DA BAHIA, BRASIL - Barbosa, J. S. F.; Silva, F. C. A.; Fornari, A.; Leite, C. M. M.; Pinho, I. C. A. (Geochimica Brasiliensis, 2011)